New records of crustose lichen species for Iran and Asia - Baradaran, Bahram; Saadatmand, Sara; Moniri, Mahroo Haji; Asri, Yunes (Acta Biologica Szegediensis, 2023)
The Khorasan-Razavi Province in northeastern Iran boasts a diverse lichen flora, fostered by its climatic diversity and extensive calcareous substrates, which provide an ideal habitat for crustose saxicolous lichens. However, the distribution of these lichens in this province has remained inadequately explored. Thus, this study aims to conduct a taxonomic investigation of crustose saxicolous lichens within this area. Between 2018 and 2019, we employed survey methods to collect 436 rock substrates from 44 locations within the province. Lichen specimens were meticulously examined, considering their morphological, anatomical, and ecological attributes. Light microscopy was utilized to scrutinize morphological and anatomical features, with a specific focus on the thallus and perithecium. Our findings reveal the first-ever documentation of the species Caloplaca atroalba (Tuck) Zahlbr. (1930) in Asia. Additionally, we report the presence of the species Pyrenodesmia micromontana (Frolov, Wilk, and Vondrák) Hafellner & Türk (2016), Arthonia mediella Nyl. (1859), Lecania erysibe (Ach.) Mudd (1861), Placopyrenium canellum (Nyl.) Gueidan & Cl. Roux, Verruculopsis minutum (Hepp.) Krzewicka, and Involucropyrenium waltheri (Kremp.) Breuss, along with the genus Involucropyrenium, as new records for the Iranian flora.